2022
DOI: 10.3389/fonc.2022.1012889
|View full text |Cite
|
Sign up to set email alerts
|

Renal insufficiency predicts worse prognosis in newly diagnosed IgD multiple myeloma patients

Abstract: ObjectiveIgD multiple myeloma (MM) is a rare type of MM, accounting for about 1%–2% of all MMs. IgD MM always causes kidney damage and even leads to renal failure, which is the most common complication. This study aimed to explore the risk factors of renal damage and prognosis of IgD MM patients.DesignFrom March 2018 to November 2021, 85 patients with IgD MM diagnosed for the first time at the First Affiliated Hospital of Zhengzhou University were included in this study. We collected information on clinical fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…IgD MM is a rare type of MM much more common in the Asian population (9,10). It currently develops at a younger age, predominantly males, with a median age of onset of 58 years (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IgD MM is a rare type of MM much more common in the Asian population (9,10). It currently develops at a younger age, predominantly males, with a median age of onset of 58 years (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Asthenia, weakness, pallor, and bone pain are the most early manifestations (7). The risk of renal damage in IgD MM is increasing and the patients with renal impairment tend to be younger (10). According to the litterature, renal failure is present in 20% to 40% of patients at the time of diagnosis (7) while primary kidney involvement and severe renal insu ciency are seen in only 15% to 20% of cases (4,11,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With these results, it was observed that the gender distribution was slightly different from some studies 17-18-19 . The frequency of RF in those with MM changes between 20-50% depending on the description of RF 4,5 . In this study, we accepted the KD limit of 1.3 mg / dl and above and percentage of KD in MM patents was 45%.…”
Section: Discussionmentioning
confidence: 99%
“…Renal failure is a common complication of MM and is among the essential causes of mortality and morbidity. While it is seen in approximately 30% of patients at diagnosis this rate can be as high as 50% during the disease course [4][5] . Although it is generally moderate, approximately 10% of patients require renal replacement therapy 6 .…”
Section: Introductionmentioning
confidence: 99%